A comprehensive approach for the production of carbon fibre-reinforced polylactic acid filaments with enhanced wear and mechanical behaviour - Radzuan Nabilah Afiqah Mohd; Samudin Izzat Mat; Sereshk Mohammad Reza Vaziri; Ma Quanjin; Sulong Abu Bakar; Foudzi Farhana Mohd; Royan Nishata Royan Rajendran (e-Polymers)
Precise control of filament parameters, including material composition and printing orientation, enables the alignment of carbon fibres (CFs) in a single orientation in additive manufacturing processes. This study reveals that printing in 0° orientation enhances both tribological and mechanical properties in CF reinforced polylactic acid composites. By fabricating in-house filaments with CFs, superior flexural, impact, and tensile strength were achieved, with improvements of ∼75% compared to conventional filaments. Findings also reveal that 0° orientation improves the printed layups in terms of interfacial bonding and adhesion within the layup sequence. It highlights the precise adjustment parameter in polymer composite filament with fibre filler, opening possibilities for advanced structures with integrated programmable functionalities in 4D printing applications.